2019
DOI: 10.1186/s13054-019-2509-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions aimed at healthcare professionals to increase the number of organ donors: a systematic review

Abstract: Background The last decade, there have been many initiatives worldwide to increase the number of organ donors. However, it is not clear which initiatives are most effective. The aim of this study is to provide an overview of interventions aimed at healthcare professionals in order to increase the number of organ donors. Methods We systematically searched PubMed, EMBASE, CINAHL, PsycINFO, and the Cochrane Library for English language studies published until April 24, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 48 publications
0
23
0
2
Order By: Relevance
“…Eightyfive participants were excluded because of missing information on exposure and covariates. Since there were no missing data on other characteristics, the participants who were included in the main analysis were the same as those with complete data (Figure 1 For the lowest (n=512), middle (n=428), and highest (n=250) tertile groups, the median (IQR) knowledge scores were 12 (11-13), 14 (14-15), and 16 (16)(17), respectively. Participants with the highest tertile of knowledge were more likely to be older female medical staff.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eightyfive participants were excluded because of missing information on exposure and covariates. Since there were no missing data on other characteristics, the participants who were included in the main analysis were the same as those with complete data (Figure 1 For the lowest (n=512), middle (n=428), and highest (n=250) tertile groups, the median (IQR) knowledge scores were 12 (11-13), 14 (14-15), and 16 (16)(17), respectively. Participants with the highest tertile of knowledge were more likely to be older female medical staff.…”
Section: Participantsmentioning
confidence: 99%
“…The major barriers to deceased organ donation are, in general, lack of knowledge about deceased organ donation and transplantation, religious and cultural perspectives, and mistrust about organ transplantation and the criteria applied for the definition of brain death [10][11][12]. These barriers could be potentially overcome through identification of potential organ donors and donation requests, family support in the intensive care unit, education, social media, and law enforcement (opt-out system) [13][14][15][16]. Among these, education of both the healthcare professionals and the general public is a key factor in enhancing organ donor registration [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reiterated the lack of good evidence describing interventions for healthcare professionals that lead to higher numbers of organ donors (Witjes et al, 2019). Nonetheless, Designated Requesters continue to be actively promoted as a positive intervention to achieve desired consent rates at transplant conferences.…”
Section: The United States Context and The Designated Requester Rolementioning
confidence: 99%
“…In summary, overall we found a lack of rigorous evidence to show that Designated Requesters are more effective than other types of health service personnel in gaining consent for organ donation. A recent systematic review reiterated the lack of good evidence describing interventions for healthcare professionals that lead to higher numbers of organ donors (Witjes et al., 2019). Nonetheless, Designated Requesters continue to be actively promoted as a positive intervention to achieve desired consent rates at transplant conferences.…”
Section: Introductionmentioning
confidence: 99%
“… Background: Globally there have been many initiatives to enhance the number of organ donors. 1 The number of individuals waiting for a transplant is significantly higher than the number of available donated organs and the gap continues to widen. In the United States, it has been reported that over 106,000 individuals are awaiting organ donation.…”
mentioning
confidence: 99%